Carbon monoxide inhibits T cell activation in target organs during systemic lupus erythematosus. (7th July 2015) - Mackern‐Oberti, J. P.; Obreque, J.; Méndez, G. P.; Llanos, C.; Kalergis, A. M.
Summary Systemic lupus erythematosus is characterized by the presence of circulating anti‐nuclear antibodies (ANA) and systemic damage that includes nephritis, haematological manifestations and pulmonary compromise, among others. Although major progress has been made in elucidating the molecular mechanisms responsible for autoimmunity, current therapies for lupus have not improved considerably. Because the exposure of carbon monoxide (CO) has been shown to display beneficial immunoregulatory properties in different immune‐mediated diseases, we investigated whether CO therapy improves lupus‐related kidney injury in lupus mice. MRL‐Faslpr lupus mice were exposed to CO and disease progression was evaluated. ANA, leucocyte‐infiltrating populations in spleen, kidney and lung and kidney lesions, were measured. CO therapy significantly decreased the frequency of activated B220+ CD4− CD8− T cells in kidneys and lungs, as well as serum levels of ANA. Furthermore, we observed that CO therapy reduced kidney injury by decreasing proliferative glomerular damage and immune complexes deposition, decreased proinflammatory cytokine production and finally delayed the impairment of kidney function. CO exposure ameliorates kidney and lung leucocyte infiltration and delays kidney disease in MRL‐Faslpr lupus mice. Our data support the notion that CO could be explored as a potential new therapy for lupus nephritis.